Effects of moderate to vigorous intensity cycling on appetite, ad libitum energy intake and appetite-related hormones in healthy South Asian and white European men. (1st October 2021) - Benedetti, Simone; Moir, Hannah J.; Stensel, David J.; Thackray, Alice E.; Naughton, Declan; Allgrove, Judith E.
Abstract: Compensatory changes in appetite and energy intake do not appear to occur in the short-term after acute exercise; however, responses have not been compared in South Asians, a group at high risk of central obesity and type 2 diabetes, with white Europeans. This study examined appetite perceptions, energy intake and appetite-related hormones after moderate-to-vigorous intensity cycling in South Asian versus white European men. Fifteen South Asians (mean(SD) 29(8) years; 25.4(4.5) kg m −2 ) and fifteen white Europeans (33(10) years; 26.1(3.8) kg m −2 ) matched for age and body mass index completed two 7 h trials (control and exercise). Participants rested throughout both trials apart from completing 60 min cycling at 2–3 h in the exercise trial. A standardised breakfast was consumed at 0 h and an ad libitum buffet meal at 4 h. Appetite perceptions and appetite-related hormones were measured at predetermined intervals. Exercise suppressed acylated ghrelin ( d  = 0.19, P  < 0.001) and increased total peptide YY (PYY) ( d  = 0.14, P  = 0.004), insulin ( d  = 0.09, P  = 0.046) and glucose concentrations ( d  = 0.31, P  < 0.001) (main effect of trial), without stimulating compensatory increases in energy intakes in either group (group-by-trial interactions). South Asians exhibited lower absolute energy intake and higher insulin concentrations than white Europeans (main effect group d  ≥ 0.63, P  ≤ 0.003), whereas group-by-time interactions revealed lower acylated ghrelin concentrations at 3 and 4 h ( d  ≥ 0.75, P  ≤ 0.038) and higher glucose concentrations at 0.75 and 2 h ( d  ≥ 0.67, P  ≤ 0.008) in South Asian than white European men. These findings demonstrate that acute exercise induces a short-term energy deficit and similar appetite responses in South Asian and white European men.